Cystathionine-β-synthase (CBS)/H2S system promotes lymph node metastasis of esophageal squamous cell carcinoma (ESCC) by activating SIRT1. (5th January 2022) - Liu, Ya; Pan, Limin; Li, Yuxi; Deng, Yuying; Han, Xue; Fu, Han; Wang, Tianxiao
Abstract: Lymph node metastasis is a key factor of death and prognosis in patients with esophageal squamous cell carcinoma (ESCC). Previous studies have demonstrated that Cystathionine-β-synthase (CBS)/H2 S system plays important roles in progression of various cancer. However, the function and mechanism of CBS/H2 S system in lymph node metastasis of ESCC remains unclear. Here, we found that CBS was highly expressed in human ESCC tissues and closely associated with lymph node metastasis in ESCC patients. Functional studies demonstrated that CBS could significantly promote lymph node metastasis of ESCC tumor cells. In vitro, CBS knockdown inhibited tumor cell proliferation, migration and invasion, whereas CBS overexpression produced the opposite results. In vivo, downregulation of CBS distinctly inhibited ESCC tumor growth and lymphatic metastasis, as evidenced by the decreased size and weight of tumor and popliteal lymph node. Meanwhile, we also found high expression of CBS-induced ESCC angiogenesis and lymphangiogenesis in vitro and in vivo by upregulating VEGF, VEGF-C, and VEGF-D. Mechanistically, CBS up-regulated the expression of SIRT1 and thus interrupted the Notch1/Hes1 axis, which plays a crucial role in lymph node metastasis of ESCC. Moreover, it was demonstrated that H2 S derived from CBS-activated SIRT1 via increasing the NAD + /NADH ratio and promoting the phosphorylation of SIRT1. In addition, H2 S derived from CBS also enhanced SIRT1 protein stability. Taken together, these data show that the high expression of CBS/H2 S system promotes ESCC lymph node metastasis via activating SIRT1 signaling pathway and CBS could serve as a potential therapeutic target for clinical intervention in ESCC. Graphical Abstract: